2011
DOI: 10.1007/s10578-011-0220-y
|View full text |Cite
|
Sign up to set email alerts
|

Acetyl-L-Carnitine as an Adjunctive Therapy in the Treatment of Attention-Deficit/Hyperactivity Disorder in Children and Adolescents: A Placebo-Controlled Trial

Abstract: The objective of this study was to test whether a previous observed Acetyl-L-carnitine (ALC) treatment effect could be repeated in an ALC adjunctive therapy treatment trial of attention-deficit/hyperactivity disorder (ADHD) in children and adolescents. This was a six-week, randomized clinical trial undertaken in an outpatient child and adolescent clinic. Subjects included 40 outpatients (28 boys and 12 girls) between the ages of 7-13 who met the DSM-IV-TR diagnostic criteria for ADHD. All study subjects were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…Regarding these studies results, ALC alone did not improve ADHD symptoms [15], but it reduced adverse effects when taken in addition to MPH. Moreover, l-carnosine seemed to improve behavioral problems according to parents [17].…”
Section: Resultsmentioning
confidence: 76%
“…Regarding these studies results, ALC alone did not improve ADHD symptoms [15], but it reduced adverse effects when taken in addition to MPH. Moreover, l-carnosine seemed to improve behavioral problems according to parents [17].…”
Section: Resultsmentioning
confidence: 76%
“…In one previous randomized, double‐blind, placebo‐controlled double‐crossover trial of the efficacy of carnitine in the treatment of boys with attention deficit/hyperactivity disorder, the investigators found a significant decrease in attention problems and aggressive behavior in 13/24 boys with ADHD with a decrease of 20–65% (8–48 points) in responsive boys as assessed by the Child Behavior Checklist (CBCL) total problem rating scale . In a placebo‐controlled trial, the use of acetyl‐L‐carnitine as an adjunctive therapy to methylphenidate in the treatment of ADHD in children and adolescents showed no differences with the placebo plus methylphenidate group . In another multi‐site, placebo‐controlled trial of acetyl‐L‐carnitine in 112 children with ADHD, the primary intent‐to‐treat analysis of 9 DSM‐IV teacher‐rated inattentive symptoms was not significant; however, secondary analyses revealed a significant moderation by subtype with superiority of acetyl‐L‐carnitine over placebo in the inattentive type, with an opposite tendency in combined type .…”
Section: Resultsmentioning
confidence: 99%
“…However, children with ADHD-inattentive type improved significantly more on carnitine than placebo, a finding not present in ADHDcombined type. In a recent trial, L-carnitine was not effective as a complementary treatment to stimulant medication for children with ADHD [30]. Although results have not documented consistent effects on hyperactivity/ impulsivity, the attention effects, in light of the known favorable effects on cardiovascular health [31], make this a reasonable treatment to consider for those unresponsive to or unwilling to accept conventional treatment for inattentivetype ADHD.…”
Section: L-carnitinementioning
confidence: 98%